Un classement archivistique au xviiie siècle : Cîteaux et les inventaires de Jean-Baptiste Lemort - Coraline Rey (Bulletin du Centre d’Études Médiévales d’Auxerre)
This paper deals with archival classifying at Cîteaux Abbey during the eighteenth century. Traces of an eighteenth century classifying can be found on the back of each charter : date, analysis of content and shelf number. This research is also based on the study of a series of inventories. Due to paleographical and codicological analyses, we can recreate the scattered inventories, and understand the archival practices and principles chosen. We also can suggest a dating for this undertaking which encompassed all the charters of Cîteaux Abbey. Only a man worked on this undertaking : Jean-Baptiste Lemort who also was an efficient cartularist.